Community Service Project At Smes In Batam: Reviewing Financial Statements and Calculating Corporate Annual Income Tax - Felix Williansyah; Meiliana Meiliana (ConCEPt - Conference on Community Engagement Project, 2023)
Following the Decree of the Minister of Education and Culture Number 3 of 2020, Universitas Internasional Batam implements the Merdeka Belajar Kampus Merdeka (MBKM) policy. This community service project implemented MBKM policy. A team consisting of a student and a lecturer from the Undergraduate Program in Accounting conducted this project. Team members helped SMEs in Batam reviewed and improved their financial statements and calculated their annual corporate income tax. We implemented this project jointly with PT Anugerah Manajemen Abadi during the period of August to December 2022. PT Anugerah Manajemen Abadi introduced us to four SMEs with limited knowledge and human resources who needed help understanding tax regulations. Those SMEs are engaged in onion trading, machinery, freight forwarding, and housing development. The Team analyzed the financial reports presented by SMEs and adjusted them according to tax regulations (Government Regulation of The Republic of Indonesia Number 7 of 2021 about general provisions and tax procedures). Adjustments were made, among others, to expenses related to "3M" (earning, collecting, and maintaining income) by fiscal reconciliation. Based on the adjusted financial reports, the Team calculated the 2022 corporate income tax expense (PPh article 29). Moreover, the Team provided SMEs with assistance in clarifying the results of their tax reporting to the tax office, including if the tax officer required additional explanations. As a result, four SMEs, which are lacking in human resources and knowledge of taxation, can receive assistance in calculating their corporate tax expenses.